URGENSI PENGELOLAAN RUANG UDARA DALAM MENJAMIN KEAMANAN NASIONAL DITINJAU DALAM PERSPEKTIF HUKUM - Putu Sugiartha, I Gede; Sujono (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2025)
The state has full and exclusive sovereignty over its airspace. A sovereign state has the right to regulate flight routes and secure its airspace, considering the strategic nature of airspace for defense and security. Violations of Indonesian airspace by both civil and state aircraft often occur. The problem studied is how to regulate and enforce the law against violations of state sovereignty according to international law and Indonesian national law. The research method used is normative legal research with a statute approach, historical approach, conceptual approach, and comparative approach. The results of the study are presented in analytical descriptive form. The results of the study conclude that both international and national law are not firm in determining the parameters of the legal status of an aircraft, whether a state aircraft or a civil aircraft. This can cause serious problems related to the laws that should apply to the aircraft. Another important thing that needs attention is the absence of firm regulations regarding the vertical limits of airspace sovereignty. Conditions and problems in airspace require regulations regarding comprehensive integrated airspace management into an integrated effort in planning, utilizing, controlling, and supervising airspace as a single area with land and sea space and space within the earth. It is necessary to review the applicable laws and whether their implementation has been maximized and the violators have been given sanctions so that it does not happen again. Therefore, the author is very interested in discussing the urgency of airspace management in ensuring national security reviewed from a legal perspective so that violations do not occur again and strict sanctions are given so that they can be a deterrent effect for violators.